PENGARUH KAPASITAS SUMBER DAYA MANUSIA DAN PERAN AUDITOR INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN WAROPEN - Bonai, Yulens Frits; Falah, Syaikhul; Daat, Sylvia C. (Jurnal Akuntansi, Audit, dan Aset, 2019)
This study aims to examine the effect of Human Resource Capacity and the Internal Auditor’s Roleon the Quality of Local Government Financial Reports. The study was located in Waropen Regencywith a total of 34 respondents, who work in the field of finance and accounting, which is related tothe preparation of the financial statements. The SPSS application was used as an analytical tool, andthe causality type of research was used to test the effect of independent variables on dependent so thatthe assessment uses Multiple Regression Analysis. The result of this study indicate that the capacityof human resources and the role of internal auditors simultaneously influence the Quality ofWaropen District Financial Reports. In addition, from the partial influence of the Capacity ofHuman Resources to have a positive effect on the Quality of Financial Statements. While the role ofinternal auditors do not affect the Quality of Financial Statements.